An application of disruptive innovation theory to create a competitive strategy in Turkish air transportation industry - Gemici, Evrim; Alpkan, Lutfihak (ELSEVIER SCIENCE BV, 2015)
Innovation undoubtedly plays a crucial role in creating and developing of market share, revenue, growth and profit at an organizational level. Innovation strategy is considered to be one of the key elements of corporate strategies since it determines where, when and what type of innovation is needed to be implemented. In this manner, common approach tells the business leaders to listen to their customer base and direct investments in products which target desired profit margin. However, this approach ignores the emergence of disruptive forces and eventually, will cause the demise of the companies. The major focus of this study is to investigate the determining factors of embracing disruptive innovation by an incumbent, through setting up an example from the Airline Industry in Turkey. Furthermore, by doing so, the study's goal is to reveal the power of disruptive forces and investigating the rapid response given by an industry leader. In this study, qualitative case study methodology is selected since the research question is contemporary in character and the process is continual. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: innovation; disruptive innovation; incumbent's response; low-cost carrier; Turkish Airlines; TECHNOLOGIES; FAILURE; Business & Economics